Fiqih Perserikatan Wanita Dalam Politik dan Jihad - Riza Umami; Ashif Az Zafi (Al-Adalah: Jurnal Hukum dan Politik Islam, 2020)
This scientific article aims to provide understanding and knowledge to readers about the jurisprudence of women's unions in political matters and also women's unions in wars and jihad such as what is good and what Allah accepts. Because many people think that the woman is only a housewife whose job is to educate children and serve their husbands. That women are also allowed to participate in politics and jihad. And there are laws in jihad. The method used for the research of this scientific article uses a qualitative descriptive method that is the data that has been obtained by the author presented in the discussion. In obtaining data the author uses literature in the form of books and journals, and also international journals.